2011
DOI: 10.1111/j.1865-1682.2011.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Control and Eradication in the Bicol Surveillance Buffer Zone of the Philippines

Abstract: Following the onset of an epidemic of foot and mouth disease (FMD) commencing in 1994 and affecting mainly pigs in the Philippines, a National Plan for the Control and Eradication of the disease was initiated. A disease surveillance buffer zone in the southern Luzon region of Bicol was established to protect the Visayas and Mindanao from infection and enable eventual elimination of the disease in Luzon. With achievement of Office International Epizooties (OIE)-certified FMD freedom with vaccination in the Phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 8 publications
0
49
0
Order By: Relevance
“…It is widely recognized that livestock movement is probably the single most important method of transmission of FMD virus in those countries where FMD is endemic (Rosenberg et al., 1980; Rweyemamu, 1984; Fonnan, 1991; Ferris et al., 1992; Windsor et al., 2011). In an analysis of over 140 putative risk factors for FMD spread in Thailand, it was concluded that the greatest impact on reducing the spread of FMD among villages would be through strategies that reduce the likelihood of introductions through livestock purchases, and for villagers taking greater care when livestock is grazed with those from neighbouring villages, particularly when sharing common water supplies (Cleland et al., 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely recognized that livestock movement is probably the single most important method of transmission of FMD virus in those countries where FMD is endemic (Rosenberg et al., 1980; Rweyemamu, 1984; Fonnan, 1991; Ferris et al., 1992; Windsor et al., 2011). In an analysis of over 140 putative risk factors for FMD spread in Thailand, it was concluded that the greatest impact on reducing the spread of FMD among villages would be through strategies that reduce the likelihood of introductions through livestock purchases, and for villagers taking greater care when livestock is grazed with those from neighbouring villages, particularly when sharing common water supplies (Cleland et al., 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This approach provides a potential driver of FMD (Gleeson, 2002) control and eventual eradication in the region (Windsor, 2011). Although FMD has been eliminated from Indonesia and most recently the Philippines (Windsor et al., 2011), the majority of countries in south‐east and eastern Asia remain infected, many with endemic FMD (Gleeson, 2002). In recent outbreaks in the previously FMD‐free countries of Korea and Japan in 2010, viral lineage studies indicated the disease originated in south‐east Asia (Knowles et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mode of transmission remains uncertain and is discussed in relation to various reports in the literature. Although air‐borne spread of FMD has been documented and infection of the respiratory tract is often considered the most common route of entry of FMDV infection (Rushton et al., 2002; Rweyemamu et al., 2008), oral transmission may also occur, particularly in swine (Lubroth, 2002) and especially in south‐east Asia (Windsor et al., 2011). In northern Thailand where cattle and buffalo production is still free‐range and similar to that in northern Lao PDR, it was found that the risk of FMD infection increased with the number of neighbouring villages sharing a common water source for their cattle and buffalo, as this increased the chance of infection by spread of the disease between large ruminant herds of neighbouring villages (Cleland et al., 1995; Rushton et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, local disease reporting networks should be strengthened through continuing education of farmers and animal health workers and rapid disease recognition and reporting should be encouraged, together with promotion of interventions that can limit disease transmission, including isolation of sick animals where possible, limiting human and animal movement during an outbreak, and proper management of infected materials. These are essential components of successful FMD control programmes in south‐east Asia (Windsor et al., 2011). However, this study of a typical FMD ‘hotspot’ area with high large ruminant density and located in a border area where transboundary movements are common highlights the importance of regular vaccination of as many of the adult large ruminants in the area as possible, particularly towards the end of the year when rice harvesting is completed and animal sales are occurring.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Managing knowledge requires a conscious move from tacit to explicit knowledge (the subconscious to conscious). Tacit knowledge is highly personal and hard to formalize and articulate, so can be difficult to communicate, but in order for knowledge to invoke substantial change in biosecurity practices by the broader rural community, it needs to become explicit.…”
Section: Knowledge Managementmentioning
confidence: 99%